THE RELATIONSHIP OF TUMMY TIME WITH NORMAL BABIES' GROSS MOTOR DEVELOPMENT IN THE DENPASAR ASI COMMUNITY IN 2022 - Syara, Arfah May; Sulistiyani, Endah; Berampu, Sabirin; Purba, Anita Sri Gandaria (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
Introduction: Infant motor development is crucial because it bridges the movements that occur during life, produces perceptual information, provides a means to gain knowledge about the world, and allows social interaction. If the basic motor stage is not passed, then there will be obstacles in motor development. Early stimulation will be needed to optimize the growth and development of children according to their stages naturally. Tummy time is one obvious form of early stimulation for muscle tone, posture, and later development. Objective: To determine the relationship between tummy time and gross motor development of normal infants in the breastfeeding community in Denpasar. Methods: An observational study using an analytical cross-sectional study, involving 30 respondents from the breastfeeding mother community in Denpasar. Primary data was obtained through a google form using the WhatsApp blast. Data analysis used Spearman rank correlation test. Results: Showed a significant relationship between the variable doing tummy time and the variable gross motor development sitting in normal infants, whether it was seen from the strong or not the correlation (with very strong results because the correlation coefficient was close to 1), the significance of the correlation results was 0.000 (less than 0.01 and 0.05) and the direction of the correlation is positive. So, Ho is rejected and H1 is accepted. Conclusion: Tummy time is proven to have a close relationship with the achievement of normal infant gross motor development with reference to the ability to sit at the age of six months. Based on the results of the study, it is recommended to do tummy time as a form of stimulation to achieve gross motor development of babies that the public needs to know.